Integrity Monitoring Technology of Mixed Constellation of High, Medium and Low Orbit Navigation Based on Genetic Algorithm Star Selection - Zhengcheng WU; Shaojie NI; Wenxiang LIU; Wei XIAO; Zongnan LI (天地一体化信息网络)
Low-orbit satellites are widely used in communication, navigation, remote sensing and other fields, which is of great significance to meet the needs of communication and improve the accuracy of navigation and positioning.Integrity technology is an important guarantee for the safe and reliable operation of satellite navigation system.With the mature development of low orbit technology and the gradual application of a large number of low orbit satellites, it is urgent to develop the system integrity monitoring technology under the condition of mixed constellation of high and low orbits.This paper proposed a hybrid constellation integrity monitoring technology for high, middle and low orbit navigation based on genetic algorithm for star selection.On the basis of the traditional optimal geometric accuracy factor selection method, genetic algorithm was introduced to construct a fitness factor based on the linear weighted feature slope of the satellite geometric observation matrix, so as to achieve rapid convergence of user protection level to protection limit.This method further improved the integrity of the receiver by optimizing the way of star selection.Under the accuracy requirement of CAT I, for the ＆quot;BeiDou+StarNet-1＆quot; constellation, the global availability level of the proposed algorithm was 5.60%, and the enhancement effect was the best for the mid-latitude and low-latitude of the Eastern Hemisphere, which were increased by 7.01% and 6.42%, respectively.